Preliminary Study on Indicators of Indonesian Kayak Coach Decision-Making for Sport Talent Development (JURNAL PENDIDIKAN JASMANI DAN OLAHRAGA, 2026)
Talent identification and development in kayaking rely heavily on the coach decision-making. However, empirical evidence regarding the prioritization of talent indicators in developing sport contexts remains limited. This study aimed to identify and prioritize key indicators used by Indonesian kayak coaches in talent development decision-making. A qualitative research design was employed, involving 32 experienced kayak coaches selected through purposive sampling based on coaching experience, participation in national and international competitions, and expertise in coaching methodology. Indicator formulation was derived from a systematic literature review and expert evaluation, and subsequently analyzed using the Analytical Hierarchy Process (AHP) to determine the relative weight of each indicator and sub-indicator. The findings revealed that technical indicators were considered the most influential in talent identification and selection, followed by psychological and biomotor indicators. In contrast, anthropometric and physiological indicators demonstrated relatively low importance, each contributing only 6.3% to the overall decision model. This study provides novel evidence by applying a structured evidence-based decision-support approach to talent development in kayaking, a sport that remains underrepresented in talent identification research. The results highlight the effectiveness of AHP in supporting coach judgments and recommend the adoption of a weighted indicator system to enhance the accuracy and effectiveness of kayak talent development programs in Indonesia.